2012
DOI: 10.5603/fhc.2012.0055
|View full text |Cite
|
Sign up to set email alerts
|

Protein C activation peptide inhibits the expression of ICAM-1, VCAM-1, and interleukin-8 induced by TNF-a in human dermal microvascular endothelial cells

Abstract: Activated protein C (APC) is generated from the cleavage of protein C by thrombin coupled to thrombomodulin and, subsequently, is released as protein C activation peptide (papC). The aim of this study was to evaluate the effect of papC on human dermal microvascular endothelial cells (HMEC-1), activated with 5 ng/ /mL TNF-a. Flow cytometry showed that papC inhibited the expression of VCAM-1 and ICAM-1, after activation with TNF-a. Similarly, RT-PCR analysis revealed that 2 and 4 pM papC inhibited the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Endothelial cells are the target of inflammatory responses and thereby, of a number of severe disorders, including sepsis and multiple organ dysfunctions that occur via LPS stimulation (11). In this study, we detected the expression of the adhesion molecules, E-selectin and ICAM-1 in LPS-treated porcine iliac artery endothelial cells (PIECs), since the upregulation of adhesion molecules and the increased secretion of cytokines and chemokines are known to occur during endothelial cell activation (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial cells are the target of inflammatory responses and thereby, of a number of severe disorders, including sepsis and multiple organ dysfunctions that occur via LPS stimulation (11). In this study, we detected the expression of the adhesion molecules, E-selectin and ICAM-1 in LPS-treated porcine iliac artery endothelial cells (PIECs), since the upregulation of adhesion molecules and the increased secretion of cytokines and chemokines are known to occur during endothelial cell activation (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial cells are the target of inflammatory responses and thereby, of a number of severe disorders, including sepsis and multiple organ dysfunctions that occur via LPS stimulation (11). In this study, we detected the expression of the adhesion molecules, E-selectin and ICAM-1 in LPS-treated porcine iliac artery endothelial cells (PIECs), since the upregulation of adhesion molecules and the increased secretion of cytokines and chemokines are known to occur during endothelial cell activation (12)(13)(14).The evolutionary conserved family of mitogen-activated protein kinases (MAPKs) includes extracellular p38 MAPK, extracellular regulated protein kinase (ERK) and c-Jun N-terminal kinase (JNK) (15). Numerous environmental stresses, such as osmotic shock, ultraviolet irradiation, as well as LPS and pro-inflammatory cytokines, have been confirmed to activate MAPK signaling cascades in a variety of cell lines (11,16).…”
mentioning
confidence: 99%
“…Pro-inflammatory mediators, cytokines, and radical oxygen species (ROS) up-regulate the expression of ICAM-1 [Roebuck and Finnegan, 1999;Ying et al, 2009;Angel-Morales et al, 2012;Pina-Canseco Mdel et al, 2012]. In fact, an increased expression of ICAM-1 occurs in different pathological inflammatory conditions, such as psoriasis, atherosclerosis, autoimmune diseases and inflammatory bowel diseases (IBD) [Chatterjee, 1998;Metselaar and Storm, 2005;Van Assche and Rutgeerts, 2005].…”
mentioning
confidence: 99%
“…15 Although it is not fully understood how TNF-a triggers vascular damage, induction of cell adhesion molecules such as intercellular adhesion molecule-1 (ICAM-1) by TNF-a is a prerequisite step for inflammatory cell attachment, endothelial cell damage and vascular leakage. [16][17][18][19] Furthermore, another study by Jiang et al 20 showed that oral administration of YKS inhibited the development of atopic dermatitis-like skin lesions in NC/Nga model mice in association with decreased mast cell infiltration. On the basis of these studies, we hypothesized that YKS may affect mast cell/basophil function.…”
Section: Introductionmentioning
confidence: 99%